THE EFFECT OF DEEP LEARNING ON STUDENTS’ INDEPENDENT LEARNING AND RELIGIOUS ATTITUDES TOWARD ISLAM IN ISLAMIC EDUCATION CLASSES AT SDN 124 PALEMBANG - Fadhilah Izzah Khairunnisa; Abu Mansur; Asri Karolina (Jurnal Konseling Pendidikan Islam, 2026)
This study is motivated by the low level of students’ learning independence and religious attitudes in Islamic Education learning, which is still dominated by conventional methods and has not encouraged deep understanding. This study aims to analyze the effect of deep learning on students’ learning independence and religious attitudes in sixth-grade students at SDN 124 Palembang. This research employed a quantitative approach with a quasi-experimental design. The research sample consisted of sixth-grade students divided into experimental and control classes. Data collection techniques were conducted through learning independence and religious attitude questionnaires that had been tested for validity and reliability. Data analysis used inferential statistical tests including normality tests, homogeneity tests, t-tests, and F-tests. The results showed that: (1) deep learning had a significant effect on students’ learning independence; (2) deep learning had a significant effect on students’ religious attitudes; and (3) deep learning simultaneously had a positive effect on learning independence and religious attitudes. Therefore, the deep learning approach is effectively implemented in Islamic Education learning to improve the quality of student learning in elementary schools.